The Multiple Facets of Iodine(III) Compounds in an Unprecedented Catalytic Auto‐amination for Chiral Amine Synthesis. Issue 26 (9th May 2016) - Buendia, Julien; Grelier, Gwendal; Darses, Benjamin; Jarvis, Amanda G.; Taran, Frédéric; Dauban, Philippe
Abstract: Iodine(III) reagents are used in catalytic one‐pot reactions, first as both oxidants and substrates, then as cross‐coupling partners, to afford chiral polyfunctionalized amines. The strategy relies on an initial catalytic auto C(sp 3 )−H amination of the iodine(III) oxidant, which delivers an amine‐derived iodine(I) product that is subsequently used in palladium‐catalyzed cross‐couplings to afford a variety of useful building blocks with high yields and excellent stereoselectivities. This study demonstrates the concept of self‐amination of the hypervalent iodine reagents, which increases the value of the aryl moiety. Abstract : Poly‐valent iodine : The design of one‐pot reactions involving a catalytic auto C(sp 3 )−H amination followed by Pd‐catalyzed couplings has led to polyfunctionalized enantiopure amines. An iodine(III) reagent can thus be used both as an oxidant and a substrate, then as a coupling partner. The overall process reveals iodoarene‐derived oxidants to be versatile building blocks in synthesis.